Patterns in spiny dogfish consumption by sex and maturity stage relate to prey availability and environmental forcing in the Northwest Atlantic - DeVries, Caroline; Gartland, James; Latour, Robert J. (Frontiers in Marine Science, 2025)
The spiny dogfish (Squalus acanthias) is a small mesopredatory shark found in temperate and subtropical waters worldwide and is the most abundant shark within the Northwest Atlantic. Coexisting with numerous economically and ecologically important species, spiny dogfish play a key role in the ecosystem, feeding on a variety of prey including Atlantic menhaden (Brevoortia tyrannus), Atlantic herring (Clupea harengus), and longfin inshore squid (Doryteuthis pealeii), among other pelagic and demersal species. Using bottom trawl survey and stomach content data collected by the Northeast Fisheries Science Center and the Northeast Area Monitoring and Assessment Program, vector autoregressive spatiotemporal (VAST) models were applied to estimate seasonal consumption indices of key prey across space and time, with separate models based on sex and maturity status. Additionally, VAST prey species distribution models (SDMs) were constructed using data from the same surveys to calculate annualized indices of seasonal prey abundance and predator-prey overlap. Annualized indices of consumption were then assessed for potential linkages with environmental and biotic covariates using Kendall-Tau correlation coefficient and repeated-median regression. The Atlantic Multidecadal Oscillation showed the most linkages among the environmental covariates considered, particularly for immature females, mature males, and consumption of longfin inshore squid. For the biotic covariates, prey availability was often associated with consumption, with evidence of prey switching between Atlantic menhaden and Atlantic herring. These results provide a clearer understanding of the spiny dogfish’s role as a predator in a diverse and productive ecosystem and contribute to the development of a science-based approach for incorporating ecosystem considerations into management.